Effect of Different Flow Directions on Drag over Riblet - J. Wang; X. Ren; X. Li; C. Gu; M. Zhang (Journal of Applied Fluid Mechanics, 2020)
Variation in flow direction requires extensive consideration in the practical application of riblet surfaces. However, studies scarcely examine the impact of flow angle α for riblet, which is usually adopted to reduce flow drag. Accordingly, this research conducted large eddy simulation for a wide range of flow angles. We explored the effect of 0° to 90° flow angle on the surface drag change of triangular riblet. The time-averaged statistical data and instantaneous flow details indicated that skin friction is decreased with the increase in α. However, pressure drag increased much faster than the friction decrease. Result revealed that skin friction reduction by 4.537% is obtained when α=0°, and it inhibits turbulence in the spanwise direction. When α≈20°, the total drag reduction disappeared. Within this range, the deviation angle showed little influence on the total drag reduction. When α=90°, skin friction is reduced by 73.3%; however the pressure drag and total drag increased, accompanied by an increased turbulence. The flow must be nearly parallel to the riblet to achieve drag reduction. Otherwise, the transverse riblet is an effective method to increase the drag.